2004
DOI: 10.1023/b:neon.0000024219.47447.91
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Infusion of IL13-PE38QQR in the Rat Brain Stem

Abstract: Interstitial infusion of IL13-PE38QQR, a tumor specific, chimeric cytotoxin, into the rat brain stem was performed in an effort to assess safety. Six rats underwent stereotaxic cannula placement into the pontine segment of the brain stem followed by a 24-h infusion of IL13-PE38QQR (volume of infusion (Vi) 200 microl) at a concentration of 10 microg/ml. The animals were assessed neurologically and then sacrificed either immediately or after 2 weeks. All animals tolerated the infusions without exhibiting any neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…16,32 Consistent with a previous report of IL13-PE infusion in a child with a DIPG, 18 the Vd:Vi ratio in our patients was significantly lower (range 1.6–4.1). Notwithstanding the reduction in Vd:Vi ratio due to coinfusion with a lower concentration of Gd-DTPA (Case 1; Gd-DTPA infusion concentration of 1 mM), the reduced efficiency in distribution in these case is likely the result of expansion of the extracellular space due to vasogenic edema.…”
Section: Discussionsupporting
confidence: 92%
“…16,32 Consistent with a previous report of IL13-PE infusion in a child with a DIPG, 18 the Vd:Vi ratio in our patients was significantly lower (range 1.6–4.1). Notwithstanding the reduction in Vd:Vi ratio due to coinfusion with a lower concentration of Gd-DTPA (Case 1; Gd-DTPA infusion concentration of 1 mM), the reduced efficiency in distribution in these case is likely the result of expansion of the extracellular space due to vasogenic edema.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical and histologic data confirmed that CED of concentrations up to and including 10 Ag/mL of IL13-PE were well tolerated in the rat brainstem over short-term (3 days postinfusion) and long-term (28 days postinfusion) evaluations. These findings are consistent with previous short-term (<14 days) rat toxicity studies that have shown lack of toxicity with perfusion of the brainstem (48) or the striatum with IL13-PE concentrations of up to 100 Ag/mL (49,50). The delayed evidence of toxicity at the highest concentration infused of IL13-PE (10 Ag/mL) in the primate indicates that IL13-PE toxicity is likely related to nonspecific, concentration-dependent immunotoxin effects on perfused tissue and is not related to CED per se or to the total infused volume of IL13-PE.…”
Section: Current Studysupporting
confidence: 91%
“…Thomale et al 108 reported on the safe placement of up to 3 cannulas in the brainstems of rats for local drug delivery, and the drug distribution was greater in the 3-cannula group than in the 1-cannula group. Because CED can be used for the delivery of large macromolecules, such as targeted toxins or monoclonal antibodies, Souweidane et al 102 showed that the tumor-specific chimeric cytotoxin IL13-PE38QQR can be safely delivered into the rat brainstem via interstitial infusion. This recombinant cytotoxin is a combination of the cytokine interleukin-13 and the modified Pseudomonas exotoxin moiety PE A , and this chimeric cytotoxin has been shown to be highly selective for glioma cells, with proven cytotoxicity in experimental studies.…”
Section: New Therapeutic Perspective Strategiesmentioning
confidence: 99%